"Seeing to be seen": The manager's political economy of visibility in new ways of working. Issue 5 (October 2021) - Leclercq-Vandelannoitte, Aurélie
Abstract: Recent changes in the world of work have modified the conditions of the exercise of management in ways that challenge managers' traditional authority and identity, both symbolically and physically. In this context, we analyse the "visibilizing process" of managers, through which they attempt to make themselves more visible, in ways that reaffirm their authority and restore their identity as managers. To that end, we develop a Foucauldian framework on power and visibility, which sheds light on the "political economy of visibility" of the manager. We apply this framework to a case study that encouraged a re-spatialization of remote work in coworking spaces. The findings show how the manager in our case study staged his own visibility, by enhancing managerial control, to manage his invisibility and shape his intertwined identities. Through the visibilizing process, the manager legitimated his role, materialized his function, and restored his authority.